The Mediating Role of Trust in the Effect of Online Customer Reviews on Purchase Decisions : A Study on Burger Bangor Consumers in Gianyar Regency - Ni Putu Putri Anggina Sari; I Gde Ketut Warmika (Harmony Management: International Journal of Management Science and Business, 2025)
The increasing prevalence of online customer reviews has made them a critical component in consumer decision-making processes, particularly in the food and beverage sector. These reviews serve as valuable feedback, influencing both the assessment of product quality and the establishment of consumer trust. In the context of Burger Bangor in Gianyar Regency, this study aims to examine the mediating role of trust in the relationship between online customer reviews and purchasing decisions. Using a purposive sampling technique, an online survey was distributed to 100 respondents who had previously purchased Burger Bangor products. The data collected were analyzed using path analysis to test the proposed hypotheses. The findings reveal that online customer reviews significantly influence purchasing decisions by positively enhancing consumer trust. Furthermore, trust itself was found to have a strong positive effect on purchasing decisions and partially mediates the relationship between online reviews and purchasing decisions. These results highlight the importance of effectively managing online customer reviews as they not only provide crucial information to potential buyers but also play a pivotal role in building trust, which in turn influences consumer purchasing behavior. For Burger Bangor, actively responding to and leveraging these reviews can be an essential strategy for improving customer trust and increasing purchase intentions, ultimately contributing to sustained competitiveness in the food and beverage industry.